PRINSIP PENGEMBANGAN BUKU AJAR BAHASA INGGRIS PARWISATA PADA PERGURUAN TINGGI - I Putu Edi Sutrisna (Cultoure: Jurnal Ilmiah Pariwisata Budaya Hindu, 2021)
The presence of a textbook in the English learning process is very important, especially if the English learning process aims to prepare university students to be able to communicate actively in the context of the tourism industry. However, many English lecturers do not prepare and develop English textbook optimally, especially textbook that is used in teaching English for Tourism. This is mainly because the English lecturers are developing English textbook without paying much attention to basic principles underlying the process of developing a good English textbook. Therefore, from this occurrence then present study was aiming at describing principles of developing a good English text book to be used as a tool in teaching English for tourism. To fulfill this purpose of study, library research method was used to have deeper understanding toward the issue. The approach of literature research is to read, evaluate, and categorize literatures in order to determine the key characteristics of the issue being studied. From the literature study, it was found that there are several experts giving key principles underlying the process of developing a good English textbook for tourism program. Those principles were seen very beneficial as a guidance for the lecturers in developing their tourism English textbook for university students.